Reimagining Cryptogenic Stroke Care: Collaborative Care and Inpatient Insertable Cardiac Monitors for Detection of Atrial Fibrillation - Nabeel A. Herial; Daniel R. Frisch; Elan Miller; Priyadarshee Patel; Alfredo Munoz; Melissa Warren; Jane Khalife; Shyam Majmundar; Nathan Farkas; Shaista Alam; Robin Dharia; Diana Tzeng; et al. (Stroke: Vascular and Interventional Neurology)
Background Atrial fibrillation (AF) is a known risk factor of ischemic stroke, and AF‐related stroke is twice more likely to be fatal. Long‐term cardiac rhythm monitoring using insertable cardiac monitors (ICMs) has greater diagnostic yield compared with conventional monitoring in detecting AF, and the clinical utility of ICMs is established in cryptogenic stroke, strokes attributable to large‐artery atherosclerosis, and strokes attributable to small‐vessel disease. A registry‐based study was conducted to evaluate the inpatient implantation of ICMs and the feasibility of vascular and interventional neurologists as implanters using novel collaborative clinical care pathway for cryptogenic stroke. Methods Multiyear data from a hospital‐based registry at a comprehensive stroke center were reviewed to evaluate inpatient ICM implantation and test feasibility of vascular and interventional neurologists as implanters of ICMs together with cardiology using a novel collaborative care pathway. Reviewed data included the number of ICMs, implantation trend, inpatient versus outpatient setting, time to ICM implantation, inpatient workflow, including defined roles of team members, and AF detection rate. Results A total of 290 ICMs for cryptogenic stroke were implanted when patients were in the hospital and 78 as outpatients after discharge during the study period of 3 years. Most inpatient ICM implants were performed by vascular and interventional neurology (n = 181), and ICM use for cryptogenic stroke increased by 130%. The average time to inpatient ICM implant was 4.1 days, with 77% in 5 days and 95.5% within 10 days poststroke. The average time to out‐patient ICM placement was 57 days. AF detection rate of 36.5% was noted at 24 months with a collaborative care pathway. Conclusion Inpatient implantation of ICMs is feasible and was performed safely and efficiently by vascular and interventional neurology together with cardiology using a collaborative care pathway. An increase in use of ICMs and higher AF detection rates were noted. Findings support innovative efforts to improve access and close the gaps in the delivery of cryptogenic stroke care to ultimately reduce the secondary stroke burden.